Cross-Talk Between Nitrosative Stress, Inflammation and Hypoxia-Inducible Factor in Patients with Adrenal Masses - Choromańska B (Dove Medical Press, 2021)
Barbara Choromańska,1 Piotr Myśliwiec,1 Tomasz Kozłowski,1 Magdalena Łuba,1 Piotr Wojskowicz,1 Jacek Dadan,1 Hanna Myśliwiec,2 Katarzyna Choromańska,3 Katarzyna Makarewicz,4 Anna Zalewska,5 Mateusz Maciejczyk6 1 1st Department of General and Endocrine Surgery, Medical University of Bialystok, Bialystok, Poland; 2Department of Dermatology and Venereology, Medical University of Bialystok, Bialystok, Poland; 3Department of Oral Surgery, Medical University of Gdansk, Gdansk, Poland; 4Regional Centre for Transfusion Medicine in Bialystok, Bialystok, Poland; 5Experimental Dentistry Laboratory, Medical University of Bialystok, Bialystok, Poland; 6Department of Hygiene, Epidemiology and Ergonomics, Medical University of Bialystok, Bialystok, PolandCorrespondence: Mateusz Maciejczyk Email mat.maciejczyk@gmail.comBackground: Adrenal masses are the most common of all human tumors. The role of nitrosative stress and inflammation in cancer development has already been demonstrated. However, it is not known whether they are involved in the pathogenesis of adrenal tumors. The aim of the study was to investigate a cross-talk between nitrosative stress, inflammation and hypoxia-inducible factor (HIF-1α) in 75 patients with different types of adrenal masses (non-functional incidentaloma, pheochromocytoma and Cushing’s/Conn’s adenoma).Methods: The plasma concentrations of total nitric oxide (NO), S-nitrosothiols, peroxynitrite nitrotyrosine and the activity of serum myeloperoxidase (MPO) were measured spectrophotometrically, whereas concentrations of interleukin 1 beta (IL-1β), tumor necrosis factor α (TNF-α) and hypoxia-inducible factor 1 alpha (HIF-1α) were measured using commercial ELISA kits. The control group consisted of 50 healthy people matched by age and sex to the study group. The number of subjects was determined a priori based on our previous experiment (power of the test = 0.9; α = 0.05).Results: We found significantly higher nitrosative stress (↑nitric oxide, ↑peroxynitrite, ↑S-nitrosothiols and ↑nitrotyrosine) in the plasma of patients with adrenal tumors, which was accompanied by increased inflammatory (↑myeloperoxidase, ↑interleukin 1 beta and ↑tumor necrosis factor α) and hypoxia (HIF-1α) biomarkers. Peroxynitrite and nitrotyrosine were positively correlated with aldosterone level. Nitrosative stress was also associated with inflammation and HIF-1α. Interestingly, plasma nitrotyrosine and serum MPO differentiated patients with adrenal tumor from healthy individuals with high sensitivity and specificity. Moreover, using multivariate regression analysis, we showed that ONOO− and IL-1β depended on cortisol level, while ONOO−, nitrotyrosine and HIF-1α were associated with aldosterone. Unfortunately, none of the assessed biomarkers differentiated between tumor types studied, suggesting that the severity of nitrosative damage and inflammation are similar in patients with incidentaloma, pheochromocytoma, and Cushing’s or Conn’s adenoma.Conclusion: Adrenal tumors are associated with increased protein nitration/S-nitrosylation and inflammation.Keywords: adrenal tumors, nitrosative stress, nitric oxide, peroxynitrite, S-nitrosothiols, nitrotyrosine, myeloperoxidase, interleukin 1 beta, tumor necrosis factor, α hypoxia-inducible factor